2014
DOI: 10.1177/105268461402400401
|View full text |Cite
|
Sign up to set email alerts
|

A Latina Principal Leading for Social Justice: Influences of Racial and Gender Identity

Abstract: In this study, the role that racial identity plays among Latina school principals is examined through a case study of a principal in a K-3 elementary school. Based on a Latina/o critical race framework and a phenomenological research approach, the study explores the degree to which having a strong understanding of one's racial identity formation may fuel leadership practices geared toward social justice. The sociocultural and historical implications of how race, class, and gender get operationalized in the ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 25 publications
2
36
0
Order By: Relevance
“…Debra talked just briefly about gender challenges. Nonetheless, her experience portrays commonalities with other Latina women [30], who makes several sacrifices in their pursuit of a successful leadership career. Her dedication to education is also reflective of her gender since her choice of serving public urban schools is also reflected in the findings from the NLLP study.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Debra talked just briefly about gender challenges. Nonetheless, her experience portrays commonalities with other Latina women [30], who makes several sacrifices in their pursuit of a successful leadership career. Her dedication to education is also reflective of her gender since her choice of serving public urban schools is also reflected in the findings from the NLLP study.…”
Section: Discussionmentioning
confidence: 91%
“…Common characteristics among NLLP participants included formal training, demonstrated success in school in their leadership role, critical consciousness about gender and race, and principals serving changing demographics. Assumptions related to this research were present in the analysis, based both on our own experiences as a Latino principal a Latina teacher in international schools, and the racism that is commonly encountered by Latina/o principals as reported by NLLP participants serving K-12 schools [30]. This principal was also chosen because of the contrasting experiences she had growing up in an all Latino community to working, as a school leader, within a majority White community.…”
Section: Counterstories As a Methodological Toolmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has found that Latinx leaders adopt strengths-based perspectives in working with students and families, rejecting deficit perspectives about low-income, communities of color (Murakami et al, 2016;Martinez et al, 2016;Hernandez, Murakami, & Quijada Cerecer, 2014). As many are bilingual themselves, they understand how to harness the power of the Spanish language to support bilingual student learning (Hernandez et al, 2014;Martinez et al, 2016) or to increase the engagement of multilingual families in schools (Hernandez et al, 2014; Méndez-Morse, Murakami, Byrne-Jiménez, & Hernandez, 2015;Murakami et al, 2016;Pedroza & Méndez-Morse, 2016). Across the literature, Latinx administrators' personal experiences impacted their desire to lead for social justice (Peterson and Vergara, 2016;Murakami et al, 2016;Méndez-Morse et al, 2015;Hernandez et al, 2014).…”
Section: Culturally Responsive Leadership For Social Justicementioning
confidence: 99%
“…As many are bilingual themselves, they understand how to harness the power of the Spanish language to support bilingual student learning (Hernandez et al, 2014;Martinez et al, 2016) or to increase the engagement of multilingual families in schools (Hernandez et al, 2014; Méndez-Morse, Murakami, Byrne-Jiménez, & Hernandez, 2015;Murakami et al, 2016;Pedroza & Méndez-Morse, 2016). Across the literature, Latinx administrators' personal experiences impacted their desire to lead for social justice (Peterson and Vergara, 2016;Murakami et al, 2016;Méndez-Morse et al, 2015;Hernandez et al, 2014). Studying Latinx leader experiences across diverse regions in the US is vital to understanding their potential to impact change for all students, especially underserved Latinx students and families.…”
Section: Culturally Responsive Leadership For Social Justicementioning
confidence: 99%